2022
DOI: 10.1021/acs.cgd.1c01468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on Preferential Crystallization for the Chiral Resolution of Citrulline: Experimental, Statistical, and Molecular Dynamics Simulation Studies

Abstract: The molar fraction solubilities of L-, D-, and DL-citrulline were first determined in aqueous solutions with different concentrations of (R)-1,3-butanediol from 283.15 to 328.15 K under 101.3 kPa using the gravimetric method. Then, based on solidstate characterizations such as powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR) spectroscopy, thermal gravity analysis (TGA), differential scanning calorimetry (DSC), and ternary phase diagram, the nature of crystalline DL-citrulline was considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…However, in CCM-0.3, the randomness is completely absent, and P is ascertained as 1, accompanied by the significantly increased absolute ee values (Figure b,c,e,f) . Specifically, the direction of ee values in CCM is uniformly controlled, that is, in l -IL CM-0.3, all ee values of the nuclei are more than zero, while they are all less than zero in d -IL CM-0.3.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in CCM-0.3, the randomness is completely absent, and P is ascertained as 1, accompanied by the significantly increased absolute ee values (Figure b,c,e,f) . Specifically, the direction of ee values in CCM is uniformly controlled, that is, in l -IL CM-0.3, all ee values of the nuclei are more than zero, while they are all less than zero in d -IL CM-0.3.…”
Section: Resultsmentioning
confidence: 92%
“…However, in CCM-0.3, the randomness is completely absent, and P is ascertained as 1, accompanied by the significantly increased absolute ee values (Figure 6b,c,e,f). 70 Specifically, the direction of ee values in CCM is uniformly controlled, that is, in L-IL CM-0.3, all ee values of the nuclei are more than zero, while they are all less than zero in D-IL CM-0.3. The results confirm that CCM-0.3 can suppress the nucleation of the enantiomeric crystal with the opposite chirality to them, leading to the preferential nucleation of enantiomeric crystals with the same chirality.…”
Section: Ternary Phase Diagrammentioning
confidence: 99%
“…In recent years, more and more methods have been used to regulate crystal growth. Due to the advantages of simplicity, effectiveness, and low cost, the additives method has been extensively studied in all kinds of crystallization processes, including the regulation of crystal growth. Generally, additives play an inhibitory role among these studies, while promoting crystal growth through additives is less studied and reported .…”
Section: Introductionmentioning
confidence: 99%
“…6−9 Lu et al used solid-phase characterization by infrared spectroscopy to distinguish chiral amino acid crystals with different rotational properties. 10,11 In addition, by comparing the experimental IR spectroscopy and simulated IR spectroscopy, a new high-precision quantitative method has been developed to study the solidstate transformation process. 12,13 Zhou et al used Fourier transform infrared (FTIR) spectroscopy to conduct online concentration monitoring and supersaturation control of the antisolvent crystallization process of paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a multitude of PAT tools have been developed for application in the regulation of crystallization operating parameters . Spectroscopy, such as infrared (IR) spectroscopy and Raman spectroscopy, has been widely applied to monitor solute concentration changes in crystallization processes. Lu et al used solid-phase characterization by infrared spectroscopy to distinguish chiral amino acid crystals with different rotational properties. , In addition, by comparing the experimental IR spectroscopy and simulated IR spectroscopy, a new high-precision quantitative method has been developed to study the solid-state transformation process. , Zhou et al used Fourier transform infrared (FTIR) spectroscopy to conduct online concentration monitoring and supersaturation control of the antisolvent crystallization process of paracetamol . Mark et al utilized in situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy to monitor the concentration of benzoic acid in solution to control the degree of supersaturation, which improved product growth and particle size .…”
Section: Introductionmentioning
confidence: 99%